Loneliness in older adult mental health services during the COVID‐19 pandemic and before: Associations with disability, functioning and pharmacotherapy. (12th October 2021) - Greig, Flora; Perera, Gayan; Tsamakis, Konstantinos; Stewart, Robert; Velayudhan, Latha; Mueller, Christoph
Abstract: Objectives: Loneliness is associated with psychiatric morbidity. Restrictions placed on the population during the first COVID‐19 lockdown may have disproportionately affected older adults, possibly through increasing loneliness. We sought to investigate this by examining loneliness in referrals to mental health of older adults (MHOA) services during the first UK COVID‐19 lockdown. Methods: Referrals to MHOA services from a large South London catchment area were identified for the 16‐week period of the UK lockdown starting in March 2020 and for the corresponding period in 2019. A natural language processing algorithm identified loneliness in the patients' records. We applied logistic regression models adjusted for age, gender, ethnicity and diagnosis, to examine associations of loneliness in the study population. Results: 1991 referrals were identified, 56.9% of whom were female, with a mean age of 77.9 years. Only 26.9% occurred during the 2020 lockdown, but with a higher prevalence of loneliness (22.0 vs. 17.7%, p = 0.028). In the whole sample, loneliness was associated with non‐accidental self‐injury (Odds ratio [OR]: 1.65), depressed mood (OR: 1.73), psychotic symptoms (OR: 1.65), relationship problems (OR: 1.49), problems with daytime activities (OR: 1.36), and antidepressant use (OR: 2.11). During lockdown, loneliness was associated with non‐accidental self‐injury (OR: 2.52), problem drinking or drug‐taking (OR 2.33), and antidepressant use (OR 2.10). Conclusions: Loneliness is associated with more severe symptoms of affective illness, worse functional problems and increased use of antidepressant medication in older adults. During lockdown, loneliness in referrals to MHOA services increased and was associated with increased risk‐taking behaviour. Loneliness is a potential modifiable risk factor for mental illness, and efforts to minimise it in older adults should be prioritised as we emerge from the pandemic. Key points: During the first UK lockdown, the total number of referrals to MHOA services decreased, but the proportion experiencing loneliness increased Loneliness was associated with symptoms of depression and psychosis, with relationship or functional difficulties, and with antidepressant prescribing across the whole study group During lockdown, loneliness was associated with increasing risk‐taking behaviour such as non‐accidental self‐injury and alcohol/drug use The impact of future social distancing measures on the older adult population must be considered, with approaches to mitigate them being prioritised